Assessing the Consideration of Maslahah and Mafsadah in the Boycott of Franchise-Based Products and Services Linked to Israel in Malaysia - Ramli, Mohd Anuar; Salleh, Ahmad Dahlan; Kasa, Annuar Ramadhon; Hassan, Paiz; Yasir, Emi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article examines the implications of boycotting franchise operations in Malaysia, identified as supporters of Israeli violence, through the lens of Islamic law, particularly focusing on the concepts of maslahah (benefit) and mafsadah (harm). The objective is to develop a nuanced understanding of the decision-making process regarding such boycotts, acknowledging their extensive economic consequences on various stakeholders, including suppliers, distributors, logistics facilitators, local employees, and business owners. Utilizing a qualitative methodology, this study employs a documentation technique and content analysis to assess the balance between maslahah and mafsadah. Findings suggest that while boycotts can apply financial pressure on Israel, they inadvertently cause significant economic distress to local Malaysian businesses and result in job losses among the local workforces. Notably, the research highlights the distinct positions of Malaysian franchises, which, unlike their Israeli counterparts, generally oppose violence and contribute to Palestinian aid efforts. Consequently, based on the evaluation of maslahah and mafsadah, the article argues that boycotting such entities in Malaysia could be counterproductive, yielding more harm than benefit